Analysis of the Utilization of Productive Waqf Assets of the HMSS Sejahtera Bersama Foundation’s Palm Oil Plantation in North Singkil District: An Islamic Financial Perspective - Brampu, Irmanto; Budiasih, Yanti (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
Productive waqf represents a management scheme that enhances the economic value of waqf assets before their benefits are distributed to the community. In Indonesia, the potential of waqf is estimated at IDR 1,000 trillion, yet only about 1% has been managed productively. The limited effectiveness of waqf management, particularly at the village level, is often constrained by low literacy, weak managerial capacity, and insufficient education for nazhir. This study aims to examine the utilization of productive waqf assets in the form of oil palm plantations managed by Yayasan Himpunan Masyarakat Singkil–Subulussalam (HMSS) Sejahtera Bersama in Singkil Utara District and to assess the application of Islamic financial principles in its management. Employing a descriptive qualitative approach through interviews, direct observation, and document review, the findings reveal that the management of oil palm plantations significantly enhances the economic value of waqf assets. The benefits are allocated to social activities, religious education, community economic empowerment, business development, and institutional operations. The management adheres to Islamic financial principles by emphasizing transparency, fairness, accountability, and avoiding riba, gharar, and maysir. This study demonstrates that productive waqf can be managed both professionally and in compliance with sharia, making it a sustainable instrument for empowering the Muslim community. [Wakaf produktif merupakan mekanisme pengelolaan aset wakaf yang berorientasi pada peningkatan nilai ekonomi sebelum hasilnya disalurkan kepada masyarakat. Potensi wakaf di Indonesia diperkirakan mencapai Rp1.000 triliun, namun pemanfaatannya secara produktif baru sekitar 1%. Rendahnya efektivitas pengelolaan, khususnya di tingkat desa, sering dipengaruhi keterbatasan literasi wakaf, lemahnya manajemen, serta minimnya edukasi bagi nazhir. Penelitian ini bertujuan menganalisis pemanfaatan aset wakaf produktif berupa kebun kelapa sawit oleh Yayasan Himpunan Masyarakat Singkil–Subulussalam (HMSS) Sejahtera Bersama di Kecamatan Singkil Utara serta menilai penerapan prinsip keuangan syariah dalam pengelolaannya. Penelitian menggunakan pendekatan kualitatif deskriptif melalui wawancara, observasi, dan studi dokumen. Hasil menunjukkan pengelolaan kebun kelapa sawit mampu meningkatkan nilai ekonomi aset wakaf secara signifikan, dengan manfaat yang disalurkan untuk kegiatan sosial, pendidikan agama, pemberdayaan ekonomi, pengembangan usaha, dan operasional yayasan. Prinsip keuangan syariah dijalankan melalui penerapan transparansi, keadilan, akuntabilitas, serta menghindari praktik riba, gharar, dan maysir. Penelitian ini membuktikan bahwa wakaf produktif dapat dikelola secara profesional sekaligus sesuai syariat, sehingga berfungsi sebagai instrumen pemberdayaan ekonomi umat yang berkelanjutan.]